Assessment of Soil Nutritional Status and Leaf Nutrient Diagnosis in Grapefruit Orchards in Thai Nguyen Province - Tung Linh, Hoang; Thi Tuyet Thu, Tran; Thi Hue, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Grapefruit is one of the critical fruit crops in Thai Nguyen province, with its productivity and economical value. This study focuses on investigating the status of soil and leaf nutrients and grapefruit yield in Thai Nguyen province. Soil samples were taken from 60 grapefruit-growing gardens under commercial production (8 - 12 years old), accompanied by medium to high levels of intensive investment. The orchards were divided into two different yield groups: low yield (<28 tons/ha) and high yield (>28 tons/ha). The high-yield group exhibited higher values in several key soil parameters: pH KCl (5.07), CEC (14.28 meq/100g), available P (68.16 mg/100g), available K (55.53 mg/100g), total N (0.16%), total P (0.15%), and total K (1.11%) compared to the low-yield group. Ca, Mg, and micronutrients (Cu, Zn, B, Mo) showed no significant differences. Leaf nutrient contents in the high-yield group were 0.31% S, 3.27% Ca, and 13.15 mg/kg Zn, while the low-yield group had 0.29% S, 3.22% Ca, and 17.05 mg/kg Zn. DRIS (Diagnosis and Recommendation Integrated System) analysis identified Mo, Mg, N, and S as the primary limiting nutrients in the low-yield group. Soil and leaf analysis combined with DRIS could be a practical approach for nutrient management in grapefruit cultivation.